Adsorptive Separation of Metal Ions with Surface Modified Desmostachya bipinnata - Kour, Jagjit; Homagai, Puspa Lal; Pokhrel, Megh Raj; Ghimire, Kedar Nath (Nepal Journal of Science and Technology, 2013)
The biomass of Desmostachy bipannata (Kush, a religious plant of Hindus) was modified for the better adsorption of metal ions from aqueous solution. The FTIR and SEM images were used for the characterization of biomass. The adsorptive separation of metal ions from aqueous solution was studied with equilibrium isotherm and kinetic model. Langmuir adsorption isotherm and pseudo second order kinetic model showed better explanation for the adsorption process. The experimental results suggest that biomass from Kush can be used as an effective biosorbent for the removal of metal ions from aqueous solution. Nepal Journal of Science and Technology Vol. 13, No. 1 (2012) 101-106 DOI: http://dx.doi.org/10.3126/njst.v13i1.7448